Unveiling Perceptions on Implementation of Madrasah Education Program: Basis for Action Plan - Tadeo, Carl Patrick S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Arabic Language and Islamic Values Education has been implemented since 2008 at Olongapo City National High School (OCNHS) as part of the Madrasah Education Program for our Filipino Muslim learners. This study aimed to assess the implementation of Madrasah Education Program in a national high school and to propose an action plan. A quantitative-descriptive research design was used in the study. A survey questionnaire was answered by six (6) teachers and (1) head teacher. Respondents were chosen using purposive sampling technique. Based on the findings of the study: 1) teachers have competence on knowledge, attitude and skills, 2) school facilities provide a conducive room for learning, 3) instructional materials were updated, 4) there is no enough support from LGU and 5) DepEd properly monitors and supports the program. Teachers’ competence, school facilities, instructional materials and DepEd support are present already but the school can still innovate to reach greater heights. On the other hand, LGU support should also be sought to further involve all stakeholders in the development of the program. It is hereby recommended that the action plan devised to address the findings of the study be implemented as part of the Improvement Plan of the ALIVE Program of OCNHS.